Compostos β-enamino carbonílicos: obtenção utilizando microondas, avaliação da sua reatividade e atividade antimicrobiana - Costa, Carla Cristiane (2007)
In this work, we explored new methodologies to obtain β-enamino carbonylic compounds derived from 1,3-dicarbonyl and α-amino acids using microwave and solvent free conditions. The β-enamino carbonylic compounds were prepared by the reaction of 1,3- dicarbonyl compounds, acetilacetone, ethyl acetoacetate or ethyl 2-oxo-1- cyclopentanecarboxylate with α-amino esters hydrochlorides derived from glycine, Lalanine, L-serine and L-proline. The reactions were performed with or without solid support (K-10 or KSF) using microwave irradiation. An addition aim of this study is the investigation of the reactivity of the β-enamino carbonylic compounds, with the possibility of creating alternative synthetic routes for heterocyclic compounds. The reactivity of the acyclic β-enamino carbonylic (C,N-dinucleophiles) was evaluated by reactions with the 1,2-diketones. To evaluate the influence of the group -CHR1COOEt (N- substituted) on the reactivity of the β-enamino carbonyl compounds obtained by reduction reactions, we used NaBH4/EtOH, which is effective for the selective reduction of the derived compounds of the acetilacetone or ethyl 2-oxo-1-cyclopentanecarboxylate giving their respective β-hidroxyenamino products. The reactivity of diethyl-3-benzylamino-2-pentenedioate was also evaluated using NaBH4, where the methylene acetate fragment (-CHR1COOEt), instead of being bonded to the nitrogen atom, is bonded to the β-carbon atom. This model allows us to evaluate the complexation of the nitrogen atom and carbonyl carbon atom with the tetrahydroborate and subsequent hydride transfer allowing a comparison with the reductions mentioned previously. The antimicrobial activity of the cyclic β-enamino carbonylic coumpounds, β- hydroxyenamino and of the heterocyclic 2-pyrrolin-5-one obtained, was investigated by the Bioautography method against different indicative microorganisms.